Distribution and behaviour of reduced sulfur substances in the oligotrophic and hydrothermal waters of the Western Tropical South Pacific - Portlock, Gemma; Whitby, Hannah; Salaün, Pascal (Frontiers in Marine Science, 2024)
Reduced sulfur species (RSS) are involved in essential biological and chemical processes, including metal complexation, but little is known about their occurrence and behaviour in marine systems. Here, we present a quantitative and qualitative data set of species-specific RSS in open ocean samples collected during the GEOTRACES Tonga GPpr14 cruise, crossing differing biogeochemical provinces, from the mesotrophic Melanesian waters and the North Fiji Basin, through the hydrothermally active Lau Basin, eastward to the oligotrophic South Pacific Gyre. Using cathodic stripping voltammetry in acidified samples (pH 2), we measured the concentration of two RSS compounds whose peaks appear at potentials of -0.18 and -0.09 V in equivalents of thioacetamide (TA) and glutathione (GSH) respectively. We also recorded, in unbuffered deoxygenated samples at natural pH  8.5, the pseudopolarograms of the only RSS peak that appear at  0.52 V with those of sulfide, GSH and TA standards. 𝑅𝑆𝑆 -0.09 𝑉 2 were only present in the upper 150 m at concentrations up to 6.2 nM eq. GSH, congruent with other CSV as well as chromatography-based studies, with the presence of GSH supported by pseudopolarography. 𝑅𝑆𝑆 -0.18 𝑉 2 were detected at all depths at concentrations ranging from 48 nM to 980 nM eq. TA. Both 𝑅𝑆𝑆 -0.18 𝑉 2 and 𝑅𝑆𝑆 -0.09 𝑉 2 were present at higher levels in the hydrothermally-impacted region of the Lau Basin relative to other stations. Highest levels, along with high sulfide concentrations, were detected in a hydrothermal plume sample, indicating that hydrothermal vents are a direct or indirect source of these compounds. 𝑅𝑆𝑆 -0.18 𝑉 2 were also high throughout almost the entire water column at a station located in the North Fiji Basin. However, while a compound that is electrochemically similar to TA is often detected in marine samples, TA itself is not thought to be naturally present. This is supported by our pseudopolarograms of 𝑅𝑆𝑆 -0.52 𝑉 8.5 which often lacked the characteristic TA reduction wave but suggested the presence of other unidentified RSS compounds. The sources and sinks of these RSS compounds are discussed.